2016
DOI: 10.1186/s12967-016-1091-6
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-AA mediates mesenchymal stromal cell chemotaxis to the head and neck squamous cell carcinoma tumor microenvironment

Abstract: BackgroundThe robust desmoplasia associated with head and neck squamous cell carcinoma (HNSCC) suggests that the tumor microenvironment may be an important component in the pathophysiology of this cancer. Moreover, the high recurrence rate and poor clinical response to chemotherapy and radiation treatment further underscores that the non-cancerous cells of the microenvironment, such as mesenchymal stromal cells (MSCs), cancer associated fibroblasts (CAFs), and pericytes, may be important in the pathophysiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…The PDGFRA/JNK-1 pathway is critical in the control of apoptosis because this signaling pathway not only influences apoptosis but also fosters p21 expression and inhibits the transition from the G1 to the S phase of the cell cycle [42]. The different types of PDGFR are inducing different downstream responses; PDGFRA and PDGFRB facilitate cell growth [43], angiogenesis [44], and chemotaxis [45]. PDGFRB inhibits apoptosis and PDGFRA/B can promote cell division [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The PDGFRA/JNK-1 pathway is critical in the control of apoptosis because this signaling pathway not only influences apoptosis but also fosters p21 expression and inhibits the transition from the G1 to the S phase of the cell cycle [42]. The different types of PDGFR are inducing different downstream responses; PDGFRA and PDGFRB facilitate cell growth [43], angiogenesis [44], and chemotaxis [45]. PDGFRB inhibits apoptosis and PDGFRA/B can promote cell division [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…While studies have individually demonstrated the role of chemical (Yoon et al, 2016;Ball et al, 2007;Watts et al, 2016) and physical cues (Hadden et al, 2017;Hou et al, 2011;Vincent et al, 2013) in directing hMSC migration, there have been no studies that have comprehensively probed the collective influence of these two cues. Here, we address this question by studying epidermal growth factor (EGF)-induced chemotaxis of hMSCs through PDMS microchannels with varying substrate stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning PDGF and their receptor it was found a prognostic role of PDGF serum level in patients with OSCC and a worse prognostic of HNSCC patients induced by the presence of PDGFR-alfa expression in the tumor microenvironment [56,57].…”
Section: Growth Factors and Their Receptorsmentioning
confidence: 99%